1998
DOI: 10.1139/v98-058
|View full text |Cite
|
Sign up to set email alerts
|

The rhodium(II)-catalyzed aziridination of olefins with {[(4-nitrophenyl)sulfonyl]imino}phenyl-lambda3-iodane

Abstract: The aziridination of olefins with {(4-nitrophenylsulfonyl)imino}phenyl-λ 3 -iodane, NsNTIPh (1c), in the presence of [Rh 2 (OAc) 4 ] proceeds in yields of up to 85% when the olefin is used in large excess. Under optimized conditions, styrene (4a) is aziridinated with 1 equiv. of NsNTIPh (1c) in 64% yield with 2 mol% of catalyst. The aziridines derived from electron-rich olefins undergo ring-opening under the conditions of the aziridination and afford rearrangement products or pyrrolidines. The aziridination is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…asc.wiley-vch.de results obtained by Müller and co-workers: [30] stereospecific rhodium-catalysed aziridination was observed with alkyl-and alkyl-aryl-substituted alkenes, but not with stilbene. One can hypothesizes a radical pathway with the later, where as a spin intersystem crossing process might be operational for the other substrates.…”
Section: Full Papermentioning
confidence: 86%
“…asc.wiley-vch.de results obtained by Müller and co-workers: [30] stereospecific rhodium-catalysed aziridination was observed with alkyl-and alkyl-aryl-substituted alkenes, but not with stilbene. One can hypothesizes a radical pathway with the later, where as a spin intersystem crossing process might be operational for the other substrates.…”
Section: Full Papermentioning
confidence: 86%
“…In 1996, Müller et al. reported the first asymmetric nitrene C–H bond amination using chiral rhodium(II) dimer complexes 8 as the catalyst, albeit with modest enantioselectivity . We found that manganese–salen complex 9 having bromo substituents was a good catalyst for intermolecular benzylic and allylic C–H amination .…”
Section: Introductionmentioning
confidence: 98%
“…This reaction resulted in the scrambling of the cyclopropane stereochemistry in the aziridinated products ( 30 ), a result that is only consistent with the reversible ring fragmentation of a cyclopropyl carbinyl radical intermediate. 23 Finally, we considered the possibility that the aziridination was not proceeding via a nitrene intermediate but rather by a [3+2] cycloaddition of the carbamoyl azide followed by a photocatalytic decomposition of a 1,2,3-triazoline intermediate. 24 To test this hypothesis, we prepared norbornene-derived triazoline 31 and irradiated it for 4 h in the presence and absence of 1c (Scheme 3C).…”
mentioning
confidence: 99%